Intensity and duration of lifestyle interventions for long-term weight loss and association with mortality: a meta-analysis of randomised trials - Singh, Navneet (BMJ Open, 2019)
OBJECTIVES: To evaluate the importance of the frequency and duration of lifestyle interventions for achieving weight loss over ≥1 year and associations with all-cause mortality. DESIGN: Meta-analysis of randomised trials using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and RevMan software version 5·2 (The Nordic Cochrane Centre, The Cochrane Collaboration, Copenhagen). DATA SOURCES: MEDLINE, CENTRAL, Google and Science Direct databases alongside reference lists of appropriate articles and meta-analyses. ELIGIBILITY CRITERIA: Randomised studies published in English-language journals from 1980 to June 2018 that assessed lifestyle compared with control interventions on weight loss and that included ≥100 subjects and reported weight change and mortality for ≥1 year. DATA EXTRACTION AND SYNTHESIS: Two independent reviewers extracted data and assessed risk of bias. Data were pooled using the generic inverse-variance method and expressed as mean differences (MDs) with 95% CI and OR with 95% CI as appropriate. Heterogeneity was assessed (Cochran Q statistic) and quantified (I(2) statistic). The Grading of Recommendations Assessment, Development, and Evaluation score was used to assess the certainty of the evidence. RESULTS: 31 randomised trials with a total of 20 816 overweight or obese participants were included. 70% of participants had cardiometabolic risk factors. Body weight was lower for lifestyle intervention compared with the control at 1 year (3.63 kg, 95% CI 2.58 to 4.67) and at 3 years (2.45 kg, 95% CI 1.17 to 3.73). Weight loss at 1 year was greater in studies with >28 compared with ≤28 interventions per year (4.50 kg, 95% CI 3.03, 5.97 vs 2.38, 95% CI 0.78 to 3.98 kg, p=0.001). In all studies, there were 593 deaths (~0.3%/year). The ORs for mortality for weight loss interventions compared with the controls was 0.86 (95% CI 0.73 to 1.02), p=0.09. CONCLUSION: In predominantly healthy populations with risk factors, there is a dose response with number of lifestyle interventions and weight loss. Frequent and sustained interventions are needed to achieve a clinically significant 5% weight loss. There was insufficient evidence to reliably evaluate the benefits in persons with known cardiovascular disease or cancer. TRIAL REGISTRATION NUMBER: CRD42018095067.